Pengaruh Film Marketing Mix Terhadap Kepuasan Audience Untuk Menonton Sekuel Film "X-Men : Days of Future Past" - Alatan, Tan, Soraya Triasri (Jurnal Strategi Pemasaran, 2014)
In the world of marketing is the term marketing mix. Marketing mix is the key to success in achieving success. Marketing mix consists of product, price, place, and promotion. Product is everything that is offered to consumers. Viewing today, many films on offer, so it may be said that the film is a product. The film is currently circulating among people in the form of serialized story better known sequel. This sequel is in great demand by looking at the income earned enough to be "king" at the box office.This study aims to analyze the influence of the film marketing mix (script / genre film, actor/actress, age classification, and release strategy) to the satisfaction of the audience âX-Menâ and the intentions of the audience. This study will be conducted by distributing questionnaires to 120 audience âX-Menâ. The analysis technique used is the technique of quantitative analysis with multiple linear regression analysis method.The research results prove that there is a significant influence of the film marketing mix of audience satisfaction on the film âX-Men: Days Of Future Pastâ, but there were no significant effects of audience satisfaction of interest to watch the next film âX-Menâ.